FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN DETEKSI DINI PRA SKRINING PERKEMBANGAN BALITA DI NAGARI KINARI WILAYAH KERJA PUSKESMAS MUARA PANAS KABUPATEN SOLOK - ratna indahsari dewi; andika herlina (Stikes Syedza Saintika Padang, 2018)
ABSTRACTToddlers period is the most important in the children growth, children growth did with early detection of pre-screening with pre-screening questioner. In Village Kinari early detection of pre-screening is very bad (18,1%). The purpose of this research is to determine the correlation knowledge, attitude and the support of health care staffs with early detection of pre screening.The research method of this study is analytical with research design is crosssectional study. The Populations of this study were 310 mothers with the samples used were 31 mothers taken with simple random sampling technique. The data analysis process used is computer system. Univariate analysis used frequency distribution table and bivariat analysis used is chi Square with 95% confidence level and significant meaning (α=0,05). According to univariate analysis result 20 (64,5%) result of detection is good, had good knowledge 16 (51,6%), had possitive attitude 19 (61,3%) and had support of health care staffs 23 (74,2%). The result of bivariate analysis showed that there was a correlation knowledge with early detection of pre-sreening with p=0,018, was a correlation with attitude p=0,015 and was a corelation support of health care staffs p=0,022.Based of the research, it can be concluded that there was a correlation between knowledge with early detection of pre-screening, was a correlation between attitude with early detection of pre-screening and was a correlation between support of health care staffs with early detection of pre-screening. Hopefully for health care staffs for increase the support and early detection of pre-screening continouslyKeyword :Early detection of pre-screening; knowledge; attitude and Support of health care staffs